Biliary tract radiology - Rossi, Plinio; Bezzi, M. (Mario) (Medical radiology (Series), 1997)
This book, written by experts from a wide range of countries, provides comprehensive coverage of the role of radiology in respect of the biliary tract. Following background chapters on anatomy, each of the diagnostic imaging techniques is carefully discussed and appraised. The therapeutic approaches to the various biliary disorders, both benign and malignant, are then described in depth. Full consideration is given to newer techniques such as magnetic resonance cholangiography and percutaneous cholangioscopy. This up-to-date and well illustrated volume will prove an indispensable source of information on biliary pathology.